The Moderating Effect Of Celebrity Preferences And Hedonism Personality On The Relationship Of Perceived Instrusiveness, Consumer Attention And Purchase Intention - Tiara Nur Anisah; Miswanto Miswanto (Universitas Mercu Buana, 2021)
The study investigates the moderating effect of celebrity preference and hedonism personality on the relationship between perceived intrusiveness, consumer attention, and intention to purchase internet users by applying SOR Theory as a foundation. This study focuses on K-Popers among teenagers. A total of 400 samples were used in this study. The sample is split into two groups, with 200 samples including advertisements that fit the respondents' preferences and have a high hedonism personality and 200 samples containing advertisements that didn’t fit the respondents' preferences and have a low hedonism personality. Multi-group moderation was performed using AMOS ver.22 with the stats tools package software, and data were analyzed using IBM SPSS Statistics 16. As expected, the higher the level of distraction perceived by the user, the lower consumer attention to the advertisement. In contrast, the less distracted individuals are, the more attention they pay to commercials. Then, the more individuals pay attention to the ads, the more likely they are to make a purchase. According to additional research, celebrity preference and hedonism personality are proven to be moderate.